Psychobehavioral factors and family functioning in mucopolysaccharidosis: preliminary studies - Valle, Daniel Almeida do; Bara, Tiago dos Santos; Furlin, Vanessa; Santos, Mara Lúcia Schmitz Ferreira; Cordeiro, Mara L. (Frontiers in Public Health, 2024)
Introduction: Mucopolysaccharidoses (MPS) constitute a group of progressive and multisystemic inherited metabolic diseases that profoundly affect both the mental health of patients and the wellbeing of their families. This study aims to evaluate the impact of MPS on family functioning and related factors. Methods and Results: Twenty-five patients with MPS, including types I (n=4), II (n=11), IIIB (n=2), IVA (n=3), and VI (n=5), and their families participated in this study. The mean patient age was 13 years (standard deviation [SD]: 7.7 years). Behavioral and emotional problems were noted in 9.1% of all patients. While the type of MPS did not directly influence mental problems, the presence of neuronal involvement did (p = 0.006). Patients with MPS III exhibited difficulties primarily in emotional areas, conduct, hyperactivity, and peer problems. Importantly, both patients with MPS II and those with MPS III experienced a significant impact on communication (mean scores for communication domain: MPS II, 35.6 [SD: 24.3]; MPS III, 35.0 [SD: 22.6]); poorer communication was directly linked to worse adaptive behavior (p = 0.012), and worse adaptive behavior was associated with lower quality of life (p = 0.001). Quality of life and caregiver burden among family members did not significantly differ across MPS types; however, higher caregiver burden was negatively associated with quality of life (p = 0.002). Concerning family functioning, the most impacted domains included independence, intellectual/cultural orientation, activity/recreation, and expressiveness. Domain scores did not vary based on MPS type, treatment, or neurological involvement. Quality-of-life scores were positively associated with the cultural/intellectual domain score. Conclusion: The impacts of quality of life and family extend beyond clinical characteristics and MPS type, strongly influenced by patient cognition and communication, as well as type of family functioning, especially those with greater cultural/intellectual skills of their family members. A multidisciplinary approach addressing the broader needs of individuals with MPS becomes essential. Techniques aimed at improving communication, including prompt interventions such as speech therapy and augmentative and alternative communication strategies, can contribute to overall family functioning improvement.